Serum concentrations of acute phase proteins in hookworm (Ancylostoma sp.) infections in dogs - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Lima, Alfredo Feio da Maia [UNESP]; Santos, Gisele Junqueira dos [UNESP]; Rubio, Camila Peres [UNESP]; Santos, Talita Fausto da Motta [UNESP]; Silva, Paulo César da [UNESP]; Fagliari, José Jurandir [UNESP] (Wiley, 2012)
Hookworms are parasitic nematodes that cause anemia and intes-tinal infections in dogs, especially with large worm burdens. Theyare the main cause of cutaneous larva migrans and also eosino-philic pneumonitis in humans. Acute phase proteins are sensitivemarkers of inflammation. In this study 80 asymptomatic dogs(age: 8 months-2 years) were evaluated to detect the presence ofthe hookworm thin-shelled, morulated eggs in feces using fecalflotation. They were divided in two groups: 40 dogs with a highquantity of eggs in feces (+++) (PD) and 40 healthy dogs (HD).Blood samples were collected to evaluate the protein fractions(APPs) in serum in both groups by means of sodium dodecylsulphate-polyacrylamide gel electrophoresis (SDS-PAGE). Thisstudy was approved by the Animal Experimentation EthicsCommittee. Infected dogs showed significant increases for IgG(PD 1.79 ± 0.8 g/dL and HD 1.44 ± 0.72 g/dL, P = .04), for cerulo-plasmin concentrations (PD 19 ± 15 mg/dL and HD 5 ± 3.5 mg/dL, P = .0001), for alpha 1-acid glycoprotein concentrations (PD31.4 ± 17.9 mg/dL and HD 13.5 ± 12.1 mg/dL, P = .0001) and fora non-nominal identified protein of 23 kD (PD 641.5 ± 194.9 mg/dL and HD 519.8 ± 197.9 mg/dL, P = .007). No statistically signifi-cant differences (P > .05) in serum total protein, albumin, IgA,transferrin and haptoglobin concentrations were identifiedbetween groups. Results of this study suggest that parasite infec-tions caused by Ancylostoma sp. triggers an acute inflammatory response in dogs.